1974
DOI: 10.1177/00220345740530030401
|View full text |Cite
|
Sign up to set email alerts
|

Activity of the Digastric Muscle in Swallowing and Chewing

Abstract: Electromyographic investigation indicates that the two bellies of the digastric muscle contract simultaneously in swallowing and in the open phase of chewing. However, about the time of tooth contact in chewing the posterior belly is active, while the anterior belly usually is inactive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1
1

Year Published

1975
1975
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 15 publications
(3 reference statements)
2
11
1
1
Order By: Relevance
“…Electromyographic data nevertheless confirm that there is synchronized activity in the two bellies during all mandibular movements, chewing, and swallowing (Munro, 1972;Munro, 1974;Yemm, 1977). Munro (1974) and Widmalm etal. (1987) both reported that occasionally activity can be nonsynchronous, but it is hard to postulate how this translates into any functional advantage other than selective control over the hyoid bone.…”
Section: Digastricmentioning
confidence: 72%
See 1 more Smart Citation
“…Electromyographic data nevertheless confirm that there is synchronized activity in the two bellies during all mandibular movements, chewing, and swallowing (Munro, 1972;Munro, 1974;Yemm, 1977). Munro (1974) and Widmalm etal. (1987) both reported that occasionally activity can be nonsynchronous, but it is hard to postulate how this translates into any functional advantage other than selective control over the hyoid bone.…”
Section: Digastricmentioning
confidence: 72%
“…In practice, this is quite difficult to confirm because electrodes must be inserted with precision into both bellies, and it has not been attempted often. Electromyographic data nevertheless confirm that there is synchronized activity in the two bellies during all mandibular movements, chewing, and swallowing (Munro, 1972;Munro, 1974;Yemm, 1977). Munro (1974) and Widmalm etal.…”
Section: Digastricmentioning
confidence: 73%
“…Our study discovered that axon collaterals from labeled genioglossus premotor neurons also innervate MoV motoneurons supplying the jaw-opening anterior digastric muscles, as well as the motoneurons located in the central part of the MoVII. The central MoVII supplies the posterior digastric muscle (jaw-opening and swallowing), the platysma muscle (which depresses the jaw and draws down the lower lip), and the lower lip muscle (Munro, 1974; Ashwell, 1982; Hinrichsen and Watson, 1984), which are all activated when the tongue is protruding (Figure 5). Additionally, we found that axon collaterals from labeled masseter premotor neurons also innervate motoneurons located in the dorsal MoXII, previously shown to innervate tongue-retractor muscles (McClung and Goldberg, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Electrodes were positioned using techniques previously described by others [ 18,19,20,21] and tested in cadavers by us. Two electrodes, 1 cm apart, were placed in each muscle.…”
Section: Data Collection Electromyography (Emg)mentioning
confidence: 99%